First case report of atypical disseminated cutaneous leishmaniasis in an opium abuser in Iran - Hashemi, Seyed Ahmad; Badirzadeh, Alireza; Sabzevari, Sadaf; Nouri, Ali; Seyyedin, Mohammad (Revista do Instituto de Medicina Tropical de São Paulo, 2018)
Leishmaniasis is a worldwide tropical infectious disease caused by different species of intracellular protozoa parasites of the genus Leishmania . Herein, we report a 78-year-old man with unusual diffuse cutaneous leishmaniasis (DCL) who had a history of opium abuse and chronic obstructive pulmonary disease (COPD). He had multiple papular, crusted and severely ulcerated lesions extended to his arm and chest. Direct smears and skin punch biopsy of the lesions were suggestive of leishmaniasis. Parasite DNA was amplified from ulcers, and identified as Leishmania major by PCR-RFLP, confirmed by sequencing analyses. The aim of the current study was to bring to attention this atypical form of disease in CL endemic countries. Thus, this is the first case of DCL in an opium abuser with COPD due to L. major in Northeastern Iran indicating that atypical and extensive forms of CL (DCL) owing to L. major are increasing in Iran.